Pelaksanaan Kursus Calon Pengantin Sebelum Pernikahan Dalam Mengatasi Problematika Rumah Tangga (Studi di KUA Kecamatan Jambi Luar Kota) - Lisa Afrianti; Umar Yusuf; Siti Marlina (NALAR FIQH: Jurnal Hukum Islam, 2022)
The background of this paper is the many problems that occur in the household which cannot be resolved properly leading to divorce. The pre-marital course program created by the Director General of Islamic Community Guidance (Dirjen Bimas Islam) aims to create a sakinah family by providing knowledge, understanding and skills in married life. This thesis uses a qualitative approach with data collection methods through observation, interviews and documentation. Based on the research conducted, the following results and conclusions were obtained: first, the implementation of the course for prospective brides at KUA, Jambi Outer City District, was carried out following the regulations made by the Director General of Islamic Community Guidance, but the implementation was not optimal. The two supporting factors in the implementation of this pre-marital course are the strategic location of the KUA, the existence of a place to carry out pre-marital courses, the presence of speakers and the presence of participants who take part in the implementation of suscatin, and the inhibiting factor in the implementation of this pre-marital course is the large number of people who do not know about the importance following this activity and the large number of people who are indifferent to the rules made by the Director General of Islamic Community Guidance regarding the obligation to take part in the implementation of this pre-marital course, so that many people are lazy and often arrive late when the course for future brides is carried out. The third impact of implementing the bride and groom course is that the participants from the implementation of the bride and groom course gain knowledge and experience that they have never previously known and the knowledge they gain during the training they practice in their household life, so that the household life they get it now to be a sakinah, mawaddah and rahmah family.